THE EFFECT OF TRANSFORMATIONAL LEADERSHIP AND WORK MOTIVATION ON TEACHER PERFORMANCE THROUGH TEACHER DISCIPLINE - Marlina, Dina; Suriansyah, Ahmad; Metroyadi (Journal of K6, Education and Management, 2019)
This research describes the transformational leadership behavior, work motivation, teacher performance, and work discipline. It also considers the effect of transformational leadership behavior on work motivation; on work discipline; and teacher performance; effect of work motivation on teacher performance; the effect of work discipline on teacher performance; the effect of transformational leadership on teacher performance through work motivation; as well as the effect of transformational leadership on teacher performance through work discipline. The research uses a quantitative approach with descriptive methods involving a research sample of 105 people. The questionnaire was used as a data collection instrument, while hypotheses were tested using path analysis. Based on the results of the research, there is; a direct effect of transformational leadership on work motivation, work discipline, and teacher performance; a direct effect of work motivation on teacher performance; an indirect effect of transformational leadership on teacher performance through work motivation; as well as an indirect effect of transformational leadership on teacher performance through work discipline. Recommendations are made for teachers to improve performance during the teaching and learning processes, while there is a need for principals to optimize their coaching methods of teachers through improved transformational leadership.